Avaliação da influência do congelamento em propriedades tecnológicas de proteínas - Borges, Willian Vieira (2023)
According to the demands for sustainable food considering the perspectives of population growth, it is believed to be convenient to investigate characteristics of foods that can serve as a nutritional alternative while simultaneously reducing environmental impacts related to traditional foods. One possibility is the study of properties of plantbased proteins as a substitute or complement to animal-based proteins. Therefore, this study aims to assess the effect of freezing on technological and spectral properties in the near-infrared region of plant-based and animal-based proteins. Spectra were collected in the near-infrared region (900 – 1700 nm), and classical methods were then used to analyze technological properties such as foam formation capacity, foam stability for 30 minutes of rest, pH, water retention capacity, oil retention capacity, and solubility. The freezing effect was evaluated at a temperature of approximately -18°C on the day of packaging opening and at intervals after 7, 14, 21, 30, 45, and 60 days. Six plant-based proteins (rice, pea, pumpkin seeds, sunflower, flaxseed, and soy) and one animal-based protein (isolated whey), all free of flavoring, stabilizing, and emulsifying substances, were evaluated. The results of technological and spectral measurements were subjected to Principal Component Analysis (PCA) to assess differences between samples and the freezing time effect. PCA indicated different behavior mainly for pea protein, distinguishing plant-based proteins from whey protein, especially regarding solubility, foam formation, and oil retention capacity. Foam formation and stability were the most affected technological properties, while pH remained stable throughout the evaluated period. The application of PCA to spectral data indicated that variations may be associated with the conformation of proteins, as the most important regions (with higher loadings) were related to N-H bonds. Additionally, there is a suggested possibility of a relationship between technological properties and the infrared region of the spectrum. However, this relationship was not explored in this study. Overall, the study indicates that freezing does not significantly influence the technological properties of the evaluated proteins.